Caspase-3 dependent nitrergic neuronal apoptosis following cavernous nerve injury is mediated via RhoA and ROCK activation in major pelvic ganglion - Hannan, Johanna L.; Matsui, Hotaka; Sopko, Nikolai A.; Liu, Xiaopu; Weyne, Emmanuel; Albersen, Maarten; Watson, Joseph W.; Hoke, Ahmet; Burnett, Arthur L.; Bivalacqua, Trinity J. (My University, 2016)
Axonal injury due to prostatectomy leads to Wallerian degeneration of the cavernous nerve (CN) and erectile dysfunction (ED). Return of potency is dependent on axonal regeneration and reinnervation of the penis. Following CN injury (CNI), RhoA and Rho-associated protein kinase (ROCK) increase in penile endothelial and smooth muscle cells. Previous studies indicate that nerve regeneration is hampered by activation of RhoA/ROCK pathway. We evaluated the role of RhoA/ROCK pathway in CN regulation following CNI using a validated rat model. CNI upregulated gene and protein expression of RhoA/ROCK and caspase-3 mediated apoptosis in the major pelvic ganglion (MPG). ROCK inhibitor (ROCK-I) prevented upregulation of RhoA/ROCK pathway as well as activation of caspase-3 in the MPG. Following CNI, there was decrease in the dimer to monomer ratio of neuronal nitric oxide synthase (nNOS) protein and lowered NOS activity in the MPG, which were prevented by ROCK-I. CNI lowered intracavernous pressure and impaired non-adrenergic non-cholinergic-mediated relaxation in the penis, consistent with ED. ROCK-I maintained the intracavernous pressure and non-adrenergic non-cholinergic-mediated relaxation in the penis following CNI. These results suggest that activation of RhoA/ROCK pathway mediates caspase-3 dependent apoptosis of nitrergic neurons in the MPG following CNI and that ROCK-I can prevent post-prostatectomy ED.